GroundWork Environmental Justice Action Climate Change Letter to South African President Cyril Ramaphosa, December 2018. (May 2019) - Peek, Bobby
GroundWork is one of South Africa's leading environmental justice organizations and the local affiliate of Friend of the Earth. It was formed in 1999 to support people's struggles for environmental justice. In the most unequal of countries, groundWork is part of the struggle for an egalitarian society in which people can live well with each other and with the earth. The following letter was sent to South African President Cyril Ramaphosa in December 2018 urging him to take a Just Transition approach to climate change policies so that the economic and social transition eliminates poverty, improves public health, and strengthens the nation's democracy.